THEMATIC PROGRESSION IN STUDENTS’ RECOUNT TEXTS - Noviyanti Noviyanti (Journal of English and Education, 2015)
This study aims to investigate how the students organize their ideas in the texts. This study employs a qualitative case study research design. The data were obtained by collecting students’ writing products in the class. Six students’ writing products were selected from three different levels of achievement—low-, mid-, and high- achiever based on the advice from the teacher. For the framework of the text analysis, this study draws on Systemic Functional Linguistic theory, especially of thematic progressions as suggested by Halliday Mathiessen (2004). The results show that all students’ texts from all levels had acquired the main purpose and the schematic structure of a recount text. Moreover, in terms of thematic progression consistency, the most occurrence of thematic progression pattern is the reiteration pattern, followed by the zigzag pattern. Meanwhile, no occurrence of multiple theme pattern in students’ recount texts indicate that the texts are not cohesion and coherence. Based on the findings, it is recommended that the teachers pay more attention to advantages of employing thematic progressions analysis applied in English learning process to allow students to gain a better control of text organization and development. Besides, it is also suggested for further researchersto investigate the other texts or to analyze the cohesive devices beyond thematic progressions.